Pengaruh Kepemimpinan Kepala Ruangan, Beban Kerja serta Budaya Organisasi Terhadap Stres Kerja Perawat Ruang Rawat Inap RSAU dr. Esnawan Antariksa - Desi Sofiana; Sandra Dewi; Muhamad Arrozi (Syntax Corporation Indonesia, 2021)
The success of a hospital is strongly influenced by its human resources, nurses are the largest human resources in the hospital, therefore nurses are the spearhead of the hospital in the process of health services but sometimes nurses also experience stress in working, especially inpatient nurses. This study aims to influence the leadership of the head of the room, workload and culture of the organization to the work stress of inpatient room nurses hospital or space hospital. This study uses quantitative research method using causality survey approach. This suggests that workload needs to be improved on indicators measured against work stress, while for leadership and culture the organization needs to be maintained or leveled so as to lower the work stress of inpatient nurses. Based on data analysis and discussion of the results of the study, it can be concluded that the variables of leadership, workload and organizational culture directly or simultaneously affect the work stress of rsau inpatient room nurses dr. Esnawan Antariksa, which means that the better the leadership, workload and culture of the organization, the lower the work stress.